A grounded theory of inspirational coach leadership - Figgins, S. G.; Smith, M. J.; Knight, C. J.; Greenlees, I. A. (Scandinavian Journal of Medicine & Science in Sports, 2019)
The purpose of this study was to develop a grounded theory of the process of inspirational coach leadership in sport. A Straussian grounded theory methodology was used. Semi-structured interviews and focus groups were conducted with athletes (n = 22) and coaches (n = 15). Data were analyzed through a process of open and axial coding, and theoretical integration. Through the process of analysis, data were broken down into smaller units (concepts), relationships between concepts were identified, and a substantive grounded theory was developed. The grounded theory of inspirational coach leadership was built around the core category of "athlete(s) inspired through changed awareness of their capabilities." The core category was underpinned by three categories: (a) establishment of mutual trust and respect with athletes, whereby coaches need to establish trust with athletes in order to inspire athletes; (b) conditions under which inspiration has the potential to occur, which highlighted that athletes are inspired in situations where they are vulnerable or ignorant regarding their potential; and (c) coach acts to change athlete's awareness of their capabilities, which denotes the specific behaviors coaches should display to inspire athletes in such conditions. The theory also highlights that a range of contextual factors relating to the coach, athletes, and performance-environment interact to impact upon the process. The theory predicts that consistency between coach behavior and the conditions in which inspiration can occur will lead to athlete inspiration, but only if the coach has established a foundation of trust and respect with the athlete.